2023
DOI: 10.1371/journal.pmed.1004203
|View full text |Cite
|
Sign up to set email alerts
|

The impact of community-based, peer-led sexual and reproductive health services on knowledge of HIV status among adolescents and young people aged 15 to 24 in Lusaka, Zambia: The Yathu Yathu cluster-randomised trial

Abstract: Background The growing population of adolescents and young people (AYP) aged 15 to 24 in sub-Saharan Africa face a high burden of HIV in many settings. Unintended pregnancies among adolescent girls in the region remain high. Nonetheless, the sexual and reproductive health (SRH) service needs of AYP have remained underserved. We conducted a cluster-randomised trial (CRT) to estimate the impact of community-based, peer-led SRH service provision on knowledge of HIV status and other SRH outcomes, including met nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
1
4
1
Order By: Relevance
“…Despite evidence of an impact on knowledge of HIV status [ 15 ], we found no evidence that Yathu Yathu increased uptake of STI testing overall. Importantly, STI testing and treatment were only available at the local health facility.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…Despite evidence of an impact on knowledge of HIV status [ 15 ], we found no evidence that Yathu Yathu increased uptake of STI testing overall. Importantly, STI testing and treatment were only available at the local health facility.…”
Section: Discussioncontrasting
confidence: 93%
“…We did, however, observe an effect on ever STI testing among young men aged 20–24. In our primary outcome analysis, we found that Yathu Yathu had the greatest effect on knowledge of HIV status among adolescent boys [ 15 ]. These combined findings among ABYM may reflect their limited engagement with the formal health system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the review of studies on SRH services, we identified four important professional services that are indispensable in providing quality and timely SRH services to young people (Elliott et al ., 2017; Hensen et al ., 2023; Kazmerski et al ., 2017). They include, (1) Medical Laboratory services (2) Social care and justice services (3) Psycho-cognitive services and (4) doctor-provided medical care.…”
Section: Introductionmentioning
confidence: 99%